Benson Therapy Against Pain Scale in Patient with NSTEMI - Setia Aji, Tatang Kurniawan; Widodo, Taat Agung; Siwi, Adiratna Sekar (Pena Medika : Jurnal Kesehatan, 2023)
Unstable Angina Pectoris is an attack of pain or stinging in the chest, one of which is NSTEMI disorder. The number of deaths due to heart attacks is obtained at a very high rate of around 17.7 million per year and 31% of deaths in the world. NSTEMI is a disorder in which there is no unique abnormality in the heart seen from a medical examination. Performing benson therapy on the pain scale in patients with nstemi in the ICU room of Hj. Anna Lasmanah Banjarnegara Hospital. The case study used is descriptive through case studies. NSTEMI patients recorded in medical records at the Hj Anna Lasmanah Banjarnegara Hospital in 2021 were 12 patients, in 2021 there were 27 patients and in 2022 there was an increase to 31 patients. Mr. S experienced left chest pain after nursing care with benson therapy for 3 X 24 hours the pain decreased to mild and disappeared. It is necessary to implement comprehensive nursing care through benson therapy so that it can help patients in overcoming the chest pain they experience